Analysis of Leadership Correlation on Performance-Based Capitation Achievement of Puskesmas - Juniarti Juniarti; Misnaniarti Misnaniarti; Yuanita Windusari (GLOBAL HEALTH SCIENCE GROUP, 2024)
The assessment of KBK indicators is sourced from the data recorded in the BPJS Kesehatan information system, so the role of health center employees in inputting data and health services for participants is very important. There are external factors of employees that are dominant in influencing performance and can be the first focus of improvement in achieving KBK values by the management of the health center, namely leadership. The study used a quantitative research method with a cross sectional design. The sample taken in this study is health center employees in Palembang City who meet the inclusion criteria, namely 10 health centers that in March – May 2024 achieved 100% KBK for 3 consecutive months and 11 health centers that in March – May 2024 did not achieve 100% KBK for 3 consecutive months. The results of the study show that there is a leadership relationship to the achievement of capitation of health centers in Palembang City. The role of leaders is very important in supporting employee performance which will support the achievement of Puskesmas performance, including the achievement of performance-based capitation values.